Optical CAD modelling and designing of compound die using the python scripting language - Rathod, V. T.; Jha, P. K.; Sawai, N. M. (International journal on interactive design and manufacturing, 2023)
The time required to model a single component and then develop the component’s family consumes a great deal of time and is a strenuous task. This issue can be resolved by parametrizing the component and adjusting it in response to changes in the design inputs. To be feasible, this approach requires precise experimental data. This strategy of incorporating experimental data and utilising design equations in the back-end enables engineers to develop a valid model for industrial use. This is the reason for the development of the compound die parametric modeller. The modeller enables direct control over the shape and parameters of the die. This enables the user to create an accurate first design before fine-tuning it using more computationally intensive methods. The modeller is written in Python and runs within the AutoCAD environment. The approach of building a variety of compound dies is partly based on state-of-the-art parametrization techniques and makes extensive use of fundamental design variables. The modeller's design resulted in a reduction in the time required for manual modelling via an automated approach.